2001
DOI: 10.1292/jvms.63.827
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoproliferative Responses in Pigs Infected with Mycobacterium avium.

Abstract: ABSTRACT. Naturally infected cases of swine mycobacteriosis were divided into two groups, localized infection (LI) and disseminated infection (DI). Lymphoproliferative response (LPR) was then examined to estimate their immunological states. Both control and LI groups showed strong response to Concanavalin A (Con A) and phytohemagglutinin (PHA) in the LPR, and lymphocytes recovered from the LI responded well to purified protein derived from M. avium (PPD). On the other hand, the DI group showed weak response to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
1
0
0
1
Order By: Relevance
“…These results demonstrate that there is an influence of the Rs infection on the CMI functions. Similar suppressive e#ect on the nonspecific T mitogenic response has previously been demonstrated in mammalian infections with Mycobacterium tuberculosis [29] and M. avium [30,31]. In the last mentioned study, as well as in the present study, a specific blastogenic lymphocyte response was demonstrated that suggested a partial insensitivity of T cells.…”
Section: Discussionsupporting
confidence: 90%
“…These results demonstrate that there is an influence of the Rs infection on the CMI functions. Similar suppressive e#ect on the nonspecific T mitogenic response has previously been demonstrated in mammalian infections with Mycobacterium tuberculosis [29] and M. avium [30,31]. In the last mentioned study, as well as in the present study, a specific blastogenic lymphocyte response was demonstrated that suggested a partial insensitivity of T cells.…”
Section: Discussionsupporting
confidence: 90%
“…No entanto, pode ocorrer infecção sistêmica, com lesões em órgãos como fígado, pulmões e baço (Iwakiri et al 2001, Matlova et al 2005, Hibiya et al 2008, Ingen et al 2010.…”
Section: Introductionunclassified